Становлення та розвиток системи приват-доцентури в університетах Європи (ХІХ - початок ХХ століття) - Таможська, Ірина Володимирівна; Tamozhska, Iryna Volodymyrivna (Тернопіль : Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2017)
Розглянуто актуальні питання становлення та розвитку системи приват-доцентури в освітньому просторі Європи (другої половини ХІХ – початку ХХ ст.). Досліджено науковий дискурс поняття «приват-доцент». Доведено, що інститут приват-доцентури в зазначений період зазнавав трансформаційних процесів. З’ясовано основні причини труднощів на цьому шляху й ставлення університетських колективів до їх подолання. Зазначено, що вперше посаду приват-доцента узаконено в статуті Берлінського університету. Встановлено, що гонорар - єдине джерело заробітку для приват-доцентів.

The urgent issues of establishment of the system of privat assistant professorship in the educational space, particularly those of objective and subjective reasons that prevented significant growth of number of privat assistant professorship are presented in the article. One of the ways to solve the mentioned problems to appeal to the gained European educational experience, because the use of creative searches and finds of the predecessors about the urgent problems of training of scientific and pedagogical staff in the universities of XVIII – XIX centuries allows to draw the main trends of future development of historical and pedagogical process. It is proved that the private – docents institute tested transformational processes in the latter half of the 19th century - the early twentieth century. The main reasons for challenges in that way, as well as the university communities’ attitude to their overcoming have been identified. It is noted that for the first time a position of the privat-docents is legalized in the charter of the Berlin University. It is determined that in the ХVIII –early ХІХ century Privat Assistant Professorship Institute revealed itself widely in the German principalities and prince-electors. It is noted that the only source of income for the researchers was the fee, which was not enough for sustenance neither privat assistant professors of the second half of the ХІХ century nor privat assistant professors of the early ХХ century. It is observed that privat assistant professors adhered to the principle of «philosophand Libertati», which involved the freedom of research and teaching, and rejected scholastic. Ancient authorities were of great value to them. Ancient authorities were of great value to them. It is defined that the free privat-associate professorship was not created at any of the universities. The scientific discourse of the notion «privat-docent» is examined.
Formation and development of the privat assistant professorship system at universities of Europe (19th – early 20th century)
Keywords: HUMANITIES and RELIGION; приват-доцентура; науково-педагогічні кадри; дисертація; ступінь магістра; private assistant professorship; scientific and pedagogical staff; dissertation; master degree